FEATURES OF KARAKALPAK MELON VARIETIES WHICH ARE RECOMMENDED FOR DRYING - M.U, Karimullaeva (International Journal of Psychosocial Rehabilitation, 2020)
This paper investigates major points of the features of Karakalpak melon varieties which are recommended for drying. On this case, research has been pinpointed on melon varieties which are recommended for drying. It concludes with the points of the different outcomes and shortcomings as the whole.